2008
DOI: 10.1371/journal.pgen.1000266
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Oxidized DNA Precursors in Huntington's Disease–Like Striatal Neurodegeneration

Abstract: Several human neurodegenerative disorders are characterized by the accumulation of 8-oxo-7,8-dihydroguanine (8-oxodG) in the DNA of affected neurons. This can occur either through direct oxidation of DNA guanine or via incorporation of the oxidized nucleotide during replication. Hydrolases that degrade oxidized purine nucleoside triphosphates normally minimize this incorporation. hMTH1 is the major human hydrolase. It degrades both 8-oxodGTP and 8-oxoGTP to the corresponding monophosphates. To investigate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…It has been established that administration of 3-NP to rodents and nonhuman primates replicates most of the clinical and pathophysiological hallmarks of HD, including spontaneous choreiform and dystonic movements, frontal-type cognitive deficits, and progressive heterogeneous striatal degeneration, at least partially by apoptosis (26). We have shown that increased expression of human MTH1 in mouse striatum efficiently suppresses such striatal degeneration, accompanied by effective suppression of the 8-oxoG accumulation in the striatum induced by 3-NP (27). However, it is not clear to what extent 8-oxoG accumulated in DNA is responsible for the neurodegeneration, because MTH1 can hydrolyze oxidized forms of ATP, GTP, and dATP as well as dGTP (28).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been established that administration of 3-NP to rodents and nonhuman primates replicates most of the clinical and pathophysiological hallmarks of HD, including spontaneous choreiform and dystonic movements, frontal-type cognitive deficits, and progressive heterogeneous striatal degeneration, at least partially by apoptosis (26). We have shown that increased expression of human MTH1 in mouse striatum efficiently suppresses such striatal degeneration, accompanied by effective suppression of the 8-oxoG accumulation in the striatum induced by 3-NP (27). However, it is not clear to what extent 8-oxoG accumulated in DNA is responsible for the neurodegeneration, because MTH1 can hydrolyze oxidized forms of ATP, GTP, and dATP as well as dGTP (28).…”
Section: Introductionmentioning
confidence: 81%
“…Overexpression of human MTH1 in mouse striatum efficiently abrogates 3-NP-induced striatal degeneration accompanied by effective suppression of 8-oxoG accumulation in the striatum (27). Mth1/Ogg1-DKO mice exhibited the highest susceptibility MUTYH deficiency ameliorates 3-NP-induced motor impairments and striatal degeneration in Ogg1-KO mice.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…Disruption of this equilibrium would give rise to cell damage, elicit disorders in the physiological state and foster pathological process such as neurodegenerative disorders, and DNA 8-oxo-7,8-dihydroguanine accumulation due to the integration of oxidized nucleotide resulting from replication or due to the oxidation of DNA guanine (14). Similarly, the mitochondrial respiratory chain becomes the principal site of superoxide radical production.…”
Section: Pathogenesis Of Oxidative Stress In the Brainmentioning
confidence: 99%
“…Oxidative stress can result from exposure to stimuli that range from environmental toxins, infection and energy dysregulation to ischemia; it has been implicated in several neurodegenerative diseases, including glaucoma (Gmitterova et al, 2009). Resolution of oxidative stress can halt neurodegeneration (De Luca et al, 2008). As will be discussed at length in the section on optic nerve head, increased IOP can affect blood flow to the retina.…”
Section: Müller Gliamentioning
confidence: 99%